Learner Autonomy: Gender-Based Perception Among EFL Indonesian Students - Moch. Said Mardjuki (Indonesian Journal of EFL and Linguistics, 2018)
Learner autonomy is believed to be the contributing factor toward the students’ successful learning process. However, its implementation in Indonesia still faces some challenges regarding students’ readiness and competencies in realizing such concept. Thus, this study is aimed to investigate gender-based perceptions and attitudes among EFL Indonesian students on learner autonomy. Qualitative design in which four out of twenty respondents were selected purposively under the rationale that they demonstrated positive evidences reflected to the preliminary questionnaire results. Using semi-structured interview, the findings indicated no gender-based discrepancy in terms of learning experiences and challenges. Although individual tasks were preferred by both groups, problem-solving strategies differ in which females employed internal strategies (rescheduling and self-commitment), while males employed external strategies (learning sources and collaborative works). In conclusion, each of the autonomous learners has personal preference to deal with the encountered challenges. Further researches, thus, need to investigate the actual transparencies of their learning behavior through observation.